Further Extension of the Generalized Hurwitz-Lerch Zeta Function of Two Variables - Kottakkaran Sooppy Nisar (Mathematics, 2019)
The main aim of this paper is to provide a new generalization of Hurwitz-Lerch Zeta function of two variables. We also investigate several interesting properties such as integral representations, summation formula, and a connection with the generalized hypergeometric function. To strengthen the main results we also consider some important special cases.